Os impactos do trabalho escravo contemporâneo no meio ambiente do trabalho - Barros, Marina Dorileo (2016)
The theme of this dissertation is the work in conditions analogous to slavery and the working environment, defined in the verification of the impacts of contemporary slave labor in the working environment. The object of research is the study of work with the reduction to a condition analogous to slavery and its impact on the work environment, identifying the relationship between violations perpetrated in the cases of slave labor with the non-fulfiment of the standards of protection of the worker health and safety. The research was guided by the following specific objectives: identify the dignity of the human person as the primary basis for worker protection; present decent work, introducing the environment balanced work as one of its components; verify the working hypotheses with reduction to conditions analogous to slavery, according to the Brazilian Penal Code; understand the balanced working enviroment as a fundamental right; discuss the relationship between the worker reduction to a condition analogous to slavery and the working environment. Chapters are divided into three, which are structured as follows: The first discuss the principle of human dignity, with the changes of understanding it possessed over the years, accentuating that the principle is the essential theoretical framework to study protection of workers' rights. It points that the guarantee of human dignity and the recognition of human rights are the basis for the creation of the concept of decent work by the International Labor Organization, which is linked to the recognition of the employee's dignity. After, passes to the study of decent work, with its characterization, highlighting the health and safety of the worker. Then analyzes the work in conditions analogous to slavery, the center of research. It examine how worker protection occurs in criminal law, analyzing carefully each mean of execution. In the third chapter, a history of environmental protection is held, so that is possible to get the concept of balanced working enviroment. It is held digression about the recognition of balanced working enviroment as a fundamental right, which is essential for the development of the relationship between the working enviroment and the contemporary slave labor. Finally is made an approach related to violations to the working enviroment perpetrated in cases of conditions analogous to slavery, highlighting the role of supervision and the mechanisms that may be used to combat this practice. The methodology follows the deductive method of approach and the method of procedure used is the monographic. The research technique used is the documentary and bibliographic.